Fever, seizures and encephalopathy: From bush fires to firestorms - Prabhjot Kaur; Suvasini Sharma; Ramesh Konanki; Asuri N Prasad (Annals of Indian Academy of Neurology, 2022)
Fever-associated seizures and febrile encephalopathy are common neurological problems in children. Infections of the nervous system are responsible for the majority of cases. However, there is a spectrum of infection-associated and inflammatory conditions associated with the triad of fever, seizures, and encephalopathy. Apart from complex febrile seizures and febrile status epilepticus, fever infection-related epilepsy syndrome of childhood (FIRES), infantile hemiconvulsion hemiplegia epilepsy syndrome (IHHE), acute encephalopathy with delayed diffusion restriction (AESD), acute necrotizing encephalopathy of childhood (ANE), and reversible splenial lesion syndrome (RESLES) are age-related clinical phenotypes of fever-related epilepsy and encephalopathy. Awareness of these entities is important for appropriate diagnosis and the prompt use of immunomodulatory/immunosuppressive therapies. In this review, we discuss the pathophysiology, clinical phenotypes, and management approaches of these fever-related seizure and encephalopathy states.